Development of a Predictive Closure Depth Equation Using Field Data and Wave Refraction Modelling. Issue 1 (May 2020) - Razak, MS Ab; Khan, AR
Abstract: In any beach nourishment project, the estimate of the closure depth is the most important aspect and it can be obtained from periodical beach profile survey data and an analytical approach. In this paper, beach profile survey data of four years 2003 (before nourishment), 2005-2007 (after nourishment) and 11 beach profile chainages were analyzed to measure the closure depth using the Fixed Depth Change (FDC) method for the case study at Teluk Cempedak, Kuantan. The results from the measured closure depth were then compared to that calculated from the Hallermeier equations. The Hs0.137% wave height was determined by a wave refraction model that was developed and analyzed against offshore wave heights to predict the onshore wave heights at a depth of 10 m using Delft3D model. In comparison, the predictive equation showed an underestimate of the average closure depth of approximately 5%. This underprediction could be due to the inclusion of closure depths that are captured at the mid-zone for the chainage profiles that are located near the southern headland. Neglecting these chainage profiles lead to an over-prediction of the closure depth. This is consistent with the concept of Hallermeiers that the predictive equation determines an upper limit value of the closure depth. The new closure depth for the studied area was established and can be equated to 0.8 times Hs0.137% .